Lokakarya Perencanaan Pembelajaran Berdiferensiasi yang Berpusat Pada Anak di TK - Ongky, Ashar; Reski Idmayanti (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Differentiated learning in Kindergarten (TK) highlights approaches that consider individual differences in preschool children's learning experiences. This service aims to analyze the types of diversity of students and their needs, assess child-centered learning and school ecosystems, design child-centered learning, and design child-centered school ecosystems. The implementation strategy starts from the self, concept exploration, collaboration space, guided reflection, contextual demonstration, elaboration of understanding, connections between materials, and real action plans. The results of this service contribute to a practical understanding of the implementation of differentiated learning in kindergarten. This service also has implications for developing a curriculum that is more adaptive and responsive to the unique needs of each child. Thus, differentiated learning in kindergarten not only enriches children's learning experiences, but also creates a strong foundation for students' holistic growth and development.